Hydrophobicity and Photocatalytic Activity of a Wood Surface Coated with a Fe3+-Doped SiO2/TiO2 Film - Luning Xuan (Materials, 2018)
A Fe3+-doped SiO2/TiO2 composite film (Fe3+-doped STCF) was prepared on a wood surface via a sol⁻gel method to improve its photocatalytic activity and hydrophobicity. The structure of the composite film was analyzed by Fourier Transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). The photocatalytic activity toward degradation of methyl orange and its hydrophobic nature were investigated. The results showed that the composite film was anatase TiO2 crystal form, and the addition of Fe3+ ions and SiO2 enhanced the diffraction peaks for the anatase crystal form. The photocatalytic activity of the wood coated with the composite film was enhanced. The highest degradation percentage was at 1 wt % Fe3+ (40.37%), and the degradation ability of the wood towards methyl orange solution was further improved under acidic conditions. In addition, the composite film was hydrophobic, and the hydrophobic property was enhanced as the immersion time in the sol increased. The wood surface coated with Fe3+-doped STCF exhibited strong hydrophobicity and photocatalytic activity, which could effectively prevent moisture from adhering to the surface and degrade organic pollutants; thus, the modified wood surface had good self-cleaning function.